2014
DOI: 10.1002/alr.21460
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure and increased food allergic sensitization in U.S. children and adults

Abstract: Exposure to lead was associated with increased odds of sensitization to food allergens in adult but not children participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Pb is extremely dangerous and affects the entire organism. It accumulates in different tissues and organs, causing different diseases ranging from mental retardation, brain damage, autism, and dyslexia to allergies, paralysis, muscular weakness, and kidney damage [ 27 , 49 , 56 , 57 , 58 , 59 , 60 ]. Nonetheless, lead toxicity is the primary cause of disease outcome for many organs, and it even causes death [ 27 ].…”
Section: Air Pollution: the Role Played By Particulate Matter And mentioning
confidence: 99%
See 1 more Smart Citation
“…Pb is extremely dangerous and affects the entire organism. It accumulates in different tissues and organs, causing different diseases ranging from mental retardation, brain damage, autism, and dyslexia to allergies, paralysis, muscular weakness, and kidney damage [ 27 , 49 , 56 , 57 , 58 , 59 , 60 ]. Nonetheless, lead toxicity is the primary cause of disease outcome for many organs, and it even causes death [ 27 ].…”
Section: Air Pollution: the Role Played By Particulate Matter And mentioning
confidence: 99%
“…Two years of Pb exposure causes chronic nephropathy manifested by focal atrophy, loss of proximal tubules, and intestinal fibrosis [ 56 ]. Continued exposition to Pb may also have immunotoxic effect and in adults it is associated with sensitization to food allergens [ 57 ]. Interestingly, an increase in Pb blood levels of adult subjects is associated with increased sensitization to food allergens, with odds ratio 1.11; 95% confidence interval 1.02 to 1.22 [ 57 ].…”
Section: Air Pollution: the Role Played By Particulate Matter And mentioning
confidence: 99%
“…The impact of allergies is the decreased quality of life, increased medical costs, impaired concentration, growth and development (Sudewi et al, 2009). Previous research conducted in Medan, North Sumatera, reported that air lead levels in industrial areas in Medan had exceeded the threshold value from the government which was 2μg/m (Mener et al, 2014;Pawankar et al, 2013;Sudewi et al, 2009;Girsang, 2008). The objective of this study is to determine the correlation between blood lead levels and total immunoglobulin E level in primary school children.…”
Section: Introductionmentioning
confidence: 95%
“…The toxic effects in children can arise from the lowest level of lead concentration at 5 μg/dL to the lethal concentration at about 150 μg/dL. According to the Center for Disease Control and Prevention (CDC) the toxic effect of lead can be observed at the serum level of 5 μg/dL (Farias et al, 2014;Mener et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation